2016
DOI: 10.1039/c6ta01446a
|View full text |Cite
|
Sign up to set email alerts
|

Alkali metals as efficient A-site acceptor dopants in proton conducting BaZrO3

Abstract: In the present contribution, we assess the efficiency of the alkali metals (Na, K, Rb and Cs) as A-site acceptor dopants in proton conducting BaZrO 3 by first principles calculations. The calculated acceptor-proton complexes become weaker with increasing dopant size, with binding energies ranging from À0.33 eV for Na to À0.10 eV for Cs, which is in the range of, or even lower than, those found for B-site doped BaZrO 3 . By mapping out all relevant minimum energy pathways for the proton, we reveal that the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…For most proton conducting oxides, β hydr has been determined in the region of 0.05-0.2 [75,[77][78][79][80][81][82][83][84][85][86]. This corresponds to a volume increase of +0.25-1.0% upon hydration for a proton concentration of 10 mol%.…”
Section: Significance and Relation Between Bulk And Lattice Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…For most proton conducting oxides, β hydr has been determined in the region of 0.05-0.2 [75,[77][78][79][80][81][82][83][84][85][86]. This corresponds to a volume increase of +0.25-1.0% upon hydration for a proton concentration of 10 mol%.…”
Section: Significance and Relation Between Bulk And Lattice Expansionmentioning
confidence: 99%
“…Such defect associations will only affect the chemical expansion upon hydration if β (Acc OH O ) × and/or β (Acc v O ) • differ significantly from the corresponding chemical expansion coefficients for the isolated proton and oxygen vacancy, β OH • O and β v •• O , respectively. Although there is little data available specifically addressing the effects of different dopants on β hydr , there appears to be a general tendency for the chemical expansion coefficient upon hydration to increase with increasing dopant size [83,85]. Furthermore, such defect associations may also impose a temperature dependence on β hydr , as experiments may be conducted under conditions where the oxygen vacancies and/or protons are partially associated to the acceptors.…”
Section: Significance and Relation Between Bulk And Lattice Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially pure titanium (CP-Ti) has been routinely employed in the area of biomedical treatment over the last 40 years or so [1][2][3]. This revolutionary application was triggered due to the perceived biocompatibility and appropriate mechanical properties of CP-Ti [4][5][6], which does not cause allergy and produce human pollutants when it is used as artificial scaffold, hip joint and dental implants [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…studied Y‐doping at the A site of BaZrO 3 and found that this doping improved the proton conductivity in strained system from their DFT calculations . Løken et al., in particular, calculated hydration enthalpies of the Na‐, K‐, Rb‐, or Cs‐doped BaZrO 3 and found that hydration enthalpies became more negative with decreases in the ionic radii of dopants . Using molecular dynamics (MD) simulations of Y‐ or Zn‐doped BaZrO 3 , Kitamura et al.…”
Section: Introductionmentioning
confidence: 99%